Agenda Setting dalam Perencanaan Pembangunan Perbatasan di Kepri Tahun 2015 - Darmawan, Eki; Nurmandi, Achmad (Universitas Muhammadiyah Yogyakarta, 2015)
Bondary not only separate territories that are owned by different communities or countries but also ensure the safetyand well-being balanced between each area concerned. Riau Islands Province is leading directly adjacent to neighboringcountries such as Malaysia, Singapore, the Philippines, and Thailand. Conditions islands region in Riau (RiauIslands) are very much separated by an ocean, the area is 252 601 km2 area consisting of 1,350 islands and 96%Ocean thus making control range of the government in development planning very difficult. This study will look at howthe government’s Agenda Setting in the border area development planning Riau Islands, which will discuss the issueand political currents flow in the policy agenda to the policies made by the government of Riau islands as borderregions.The method used in this study is qualitative. The study was conducted in Regional Development PlanningBoard (Bappeda) Riau Islands Province, the Regional Border Management Agency (BNPPD) Riau Islands Provinceand Commission III of the House of Representatives (DPRD) Riau Islands Province. Data collection techniques performedin this study were interviews, collecting data document written and unwritten, and non-participant observation.Results from this study is the first, the flow of matter to explain the issues and problems that occur on the borderof Riau Islands namely the problem of limited infrastructure such as facilities and infrastructure such as facilities andinfrastructure of housing, education, health, security, and also facilities and transport infrastructure, telecommunications,and Other causes of this region have low accessibility and isolated from the surrounding region. Secondly, theflow of Politics explains the policy process and then view and objectives to be achieved still has a perception about theconstruction of the border is still different, the level of public participation, NGOs, academics and NGOs are stillrelatively low, the handling is still partial, sectoral and yet integritasi, coordination has not gone good, both amongsectoral, national level and between the central government and local governments, commitment and developmentbudget in the border area is still relatively minimal. Third, Flow Policy describes several emerging priorities namely,development of processing industry, fishery and tourism in a sustainable manner in order to support the sector ofmaritime, increasing production and agricultural productivity, as well as self-reliance and food security community,Improved connectivity between regions and between the island and the means and basic infrastructure of society,Improving the quality of the environment and forestry, natural disaster mitigation and climate change, peningatanquality human resources and well-being equitable and civilized society, Improving the quality of public services andgood governance.